The Lemko-Rusyns in the 20th Century: A Study in the Development of National Consciousness. - Best, Paul J. (1988)
Keywords: dept.psc; faculty_collection; sabbatical_report

Public Activities and Studies Related to the Social Role of People with Disabilities. - Gelbach, Robert (1988)
Keywords: dept.psc; faculty_collection; sabbatical_report

Politics in Three Worlds: An Introduction to Political Science - Best, Paul J.; Rai, Kul B.; Walsh, David F. (Wiley, 1986)
Keywords: Political science; Comparative government; Comparative economics; dept.psc; faculty_collection

The Morning Cometh: 45 Years with Anatolia College - Compton, Carl C.; Iatrides, John O.; Compton, William R. (Aristide D. Caratzas, 1986)
Keywords: 20th century; High school teachers; Biography; Biography; Anatolia College; Biography; High school teachers; Compton; Carl C; Anatolia College; Faculty; Greece; History; Turkey; dept.psc; faculty_collection

Greek-American Relations: A Critical Review - Couloumbis, Theodore A.; Iatrides, John O. (Pella Pub. Co., 1980)
SCSU Faculty Scholar Award
Keywords: Foreign relations; Greece; Greece; United States; award_winner; dept.psc; faculty_collection

Book Review: Prospects for Change in Socialist Systems: Challenges and Responses. Edited by Charles J. Bukowski and Mark A. Cichock. New York: Praeger, 1987. 151p. $34.95. - Best, Paul J. (American Political Science Review, 1989)
1 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1989T772200079 tex.unique-id: [object Object]
Keywords: book review; book.review; dept.psc

Book Review: Soviet-east european relations: consolidation and conflict, 1968-1980 . by robert l. hutchings. (madison, WI: the university of wisconsin press, 1983. pp. xvi, 314. 27.50.) - Best, Paul J (The Journal of Politics, 1986)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/126-417-814-555-404 tex.type: [object Object]
Keywords: book.review; dept.psc

Occupation and resistance - the greek agony, 1941-44 - hondros,jl - Iatrides, JO (American Historical Review, 1985)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1985ABJ9700109
Keywords: dept.psc

The United-States, Greece and Turkey - the Troubled Triangle - Couloumbis,ta - Iatrides, JO (Political Science Quarterly, 1984)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1984AAA5700043
Keywords: dept.psc

Book Review: American-intervention in greece, 1943-1949 - wittner,ls - Iatrides, John O (American Historical Review, 1983)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1983QC39200202
Keywords: book.review; dept.psc

UN voting data - Rai, Kul B (Journal of Conflict Resolution, 1982)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/094-090-879-139-726 tex.type: [object Object]
Keywords: dept.psc

Book Review: Marian rybicki, editor. sejm ustawodawczy rzeczypospolitej polskiej 1947-1952. warszawa: polska akademia nauk, 1977. 350 pp. - Best, Paul J (Canadian-american Slavic Studies, 1981)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-744-129-687-725 tex.type: [object Object]
Keywords: book.review; dept.psc

Book Review: Protest movements in two indian states: A study of the gujarat and bihar movements . by ghanshyam shah. (delhi, india: ajanta publications, 1977. pp. xi + 171. 8.00.) - Rai, Kul B (American Political Science Review, 1980)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/177-041-636-968-675 tex.type: [object Object]
Keywords: book.review; dept.psc

Foreign aid and voting in the UN general assembly, 1967—1976 - Rai, Kul B (Journal of Peace Research, 1980)
This paper examines the relationship between foreign (economic) aid and the General Assembly votes for the period 1967-76. The countries included in this study are the United States, the Soviet Union, and those of their aid recipients which are considered less developed. Two related hypotheses, one on the use of aid as an inducement and the other as a reward or a punishment, are tested. The methods used are Index of Agreement, devised by Arend Lijphart, and Pearson's r. The findings indicate that the American aid is more effective as an inducement and the Soviet aid is more effective as a reward or a punishment. The former has a closer association with the General Assembly votes from 1967-73 than in later years. Economic aid is increasingly used by the United States more to serve its security interests in the Middle East than for any other purpose, and it is possible that not so much of a return for the American aid is expected in the UN as was the case earlier. © 1980, Sage Publications. All rights reserved.
58 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/026-558-274-527-739 tex.type: [object Object]
Keywords: dept.psc